DETECTION TRACES OF SYSTEM SUBMITTING PAPER OF PRINTER DEVICES IN ORDER TO CONDUCT EXPERT STUDIES - A. Efmenko; P. Chetverkin (Теория и практика судебной экспертизы)
The methodological aspects of detecting and interpreting picture of traces leave details and nodes of systems submitting paper of modern printer devices are discussed.